PWE-018 Superiority of actual compared with close (<1 mm) circumferential resection margin involvement in the pathological staging of oesophageal and junctional cancer. (28th May 2012) - O'Farrell, N J; Donohoe, C L; Costelloe, J M; Muldoon, C; Ravi, N; Reynolds, J V
Abstract : Introduction: An involved circumferential resection margin (CRM), defined as tumour cells within 1 mm of the CRM, is of established prognostic significance in rectal cancer. In the oesophagus, which unlike rectum lacks a defined mesentery, controversy exists, with the UK Royal College of Pathologists (RCP) recommending the 1 mm definition, while the College of American Pathologists (CAP) advise that only an involved margin defines an incomplete (R1) resection. Methods: CAP and RCP CRM status were recorded prospectively in a comprehensive prospective data-base from May 2003 to May 2011. Factors impacting on survival were assessed by univariate and multivariate analysis. Kaplan–Meier survival curves for CRM + compared with CRM- groups by RCP and CAP criteria were computed. Results: RCP and CAP CRM status was available for 316 patients. Overall, positive margins were recorded in 33% (n=103) and 10% (n=33) using the RCP and CAP criteria, respectively. Specific analysis focused on 143 patients with pT3 tumours. Mean follow-up was 19.8 months (range 1.6–79.5 months). RCP criteria diagnosed 60.8% (n=87) of pT3 tumours as positive; however, by CAP criteria, 18% (n=27) were positive. A significantly higher proportion of CAP positive CRMs were associated with lymph node metastases (p=0.05). Using RCP criteria there was no significant difference in survival in patients with positive and negative CRM margins (p=0.201). However, CRM involvement by CAP criteria was associated with poor survival (p=0.003). Multivariate analysis revealed nodal invasion and CAP CRM positive disease as independent prognostic variables (p=0.047 and p=0.028 respectively). Conclusion: Comparison of the RCP and CAP criteria indicates that CAP is superior, consistent with recent data. 1 It may be best to include both assessments in prospective data-bases, but this data suggests that actual rather than close CRM involvement significantly impacts outcome, and may be factored into prognostic calculation and possibly the design of future adjuvant trials. Competing interests: None declared. Reference: 1 Deeter M, Dorer R, Kuppusamy MK, et al. Assessment of criteria and clinical significance of circumferential resection margins in esophageal cancer. Arch Surg 2009;144 :618–24.